Do Interest Rate Policy and Liquidity Effect on Banking Credit Risk in Indonesia? - Amalia, Sopira Qori; Suriani, Suriani (Signifikan: Jurnal Ilmu Ekonomi, 2023)
Lending plays a vital role for banks as a source of income from deposits or interest paid by debtors. This study aims to analyze the effect of policy interest rates and liquidity from the money supply on bank credit risk in Indonesia in the short and long term. This study uses the Autoregressive Distributed Lag method and the Granger Causality test as analytical tools. The data used are policy interest rates, total money supply, and total non-performing loans. The data period under study is 2017-2022. The study results show that in the short term, policy interest rates and the money supply negatively affect bank credit risk in Indonesia. However, in the long term, policy interest rates have a negative effect, and the money supply does not affect bank credit risk in Indonesia. Policy interest rates have a one-way causality relationship with bank credit risk. Meanwhile, bank credit risk has a one-way causality relationship to the money supply. This condition represents that policy interest rates can reduce bank credit risk in Indonesia. The Bank of Indonesia, as the monetary authority, needs to pay attention to fluctuations in policy interest rates and mitigate excess money supply so that credit risk does not increase.JEL Classification: F43, O11, P34How to Cite:Amalia, S. Q., & Suriani, S. (2023). Do Interest Rate Policy and Liquidity Affect Banking Credit Risk in Indonesia?. Signifikan: Jurnal Ilmu Ekonomi, 12(1), 145-160. https://doi.org/10.15408/sjie.v12i1.27119.